Towards a visuo-dynamic interface for disability self-assessment. - Rybarczyk, Yves Philippe; Vernay, Didier (Technology & Disability, 2018)
BACKGROUND: The Therapeutic Patient Education (TPE) aims to help patients to understand diseases and treatments, and collaborate in healthcare by taking an active role in the management of a chronic disease. This transition from the classical patient compliance to empowerment is a revolutionary concept in medicine. However, this consensual idea is not easy to implement because of the complexity of medical records, which are designed for health professionals only. OBJECTIVE: In order to enhance the TPE, an intuitive tool based on a visuo-dynamic interface was developed to facilitate the self-evaluation of disability situations. METHODS: The paper describes the whole implementation process to implement such a user interface, from the development of an innovative low cost markerless motion capture to the 3D modeling of everyday life activities. RESULTS: A usability test carried out on twenty disabled people shows that participants are more at ease to perform a self-assessment of their motor disabilities through an animated stickman-based interface than a classical static interface. CONCLUSIONS: Considering the promising results of this study, the next step of this project will consist of integrating the visuo-dynamic interface into an existing platform (e-ESPOIRS-Handi) dedicated to information sharing between health professional and disabled people.